Evaluation of the radix entomolaris canal in first molars lower: A clinical case report (Research, Society and Development, 2024)
The success of endodontic treatment is entirely related to efficient chemical/mechanical preparation, correct three-dimensional hermetic sealing of the root canal system and knowledge of anatomical variations, representing a major daily clinical challenge for endodontists. Radix entomolaris (RE) is a rare change, which can be present in the first, second and third permanent lower molars and which, if not treated correctly, can lead to failures in the treatment performed. The present study aims to present a clinical case report of element 46 (right lower first molar), which has this demarcated ER anatomical variation. With the aid of the periapical radiographic examination (diagnosis of chronic apical periodontitis), the tooth was treated endodontically, which, after completion, the patient continued to report painful symptoms, therefore, a cone beam computed tomography was requested, where, she noticed the presence of this anatomical variation, carrying out a partial retreatment and finalizing the case, continuing with its follow-up. Therefore, it is clear that morphological knowledge of the root canal systems and their alterations is essential, as well as a correct diagnosis with the aid of image exams to facilitate its location and thus obtain the expected final success.